1993
DOI: 10.1042/bj2940595
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of collagens II and XI and alternative splicing of exon 2 of collagen II in several developing human tissues

Abstract: Northern analyses, RNAase protection assays and in situ hybridizations were used to study the expression of the mRNA for the alpha 2 chain of collagen XI and the two different mRNAs generated from the collagen II gene through alternative splicing of exon 2 in several different tissues of 15-19-week-old fetuses. The highest expression levels of procollagen alpha 2(XI) and alpha 1(II) mRNAs were detected in cartilage, but, using long exposure times, Northern hybridization revealed the presence of the approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

1994
1994
1998
1998

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…This probably represents mRNAs present in prechondrogenic mesenchyme (Kravis and Upholt, 1985;Kosher et al, 1986) or mRNAs in extraskeletal locations (Cheah et al, 1991;Sandberg et al, 1993). During development, transient low level expression of type I1 collagen has been detected at several epitheliomesenchymal interfaces of the craniofacial system and in other tissues such as the notochord and the brain (Kosher and Solursh, 1989;Thorogood et al, 1986;Cheah et al, 1991;Wood et al, 1991;Sandberg et al, 1993). In the present study we have shown that the pcYl(I1)LacZ transgene is transcriptionally active in 11.5 day embryos along the prechondrogenic mesenchyme of the vertebral column (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This probably represents mRNAs present in prechondrogenic mesenchyme (Kravis and Upholt, 1985;Kosher et al, 1986) or mRNAs in extraskeletal locations (Cheah et al, 1991;Sandberg et al, 1993). During development, transient low level expression of type I1 collagen has been detected at several epitheliomesenchymal interfaces of the craniofacial system and in other tissues such as the notochord and the brain (Kosher and Solursh, 1989;Thorogood et al, 1986;Cheah et al, 1991;Wood et al, 1991;Sandberg et al, 1993). In the present study we have shown that the pcYl(I1)LacZ transgene is transcriptionally active in 11.5 day embryos along the prechondrogenic mesenchyme of the vertebral column (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Later type I1 collagen was also detected in the vitreous of the eye and the nucleus pulposus (von der Mark, 1980Mark, ,1981. During development transient occurrence of small amounts of type I1 collagen or its mRNA has been observed especially at epithelio-mesenchymal interfaces of both cartilaginous and non-cartilaginous tissues (Thorogood et al, 1986;Hayashi et al, 1988;Fitch et al, 1989;Kosher and Solursh, 1989;Cheah et al, 1991;Wood et al, 1991;Swiderski and Solursh, 1992;Sandberg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation of the differences between cartilage and cardiac extracellular matrices and their role during development and differentiation may evolve from experiments designed to study the role of the alternatively spliced exon 2 domain in type I1 collagen. This cysteine-rich amino propeptide domain is present in the ul(I1) collagen transcripts of many pre-chondrogenic and non-chondrogenic tissues including the heart (Ryan and Sandell, 1990;Cheah et al, 1991;Metsaranta et al, 1991;Nah and Upholt, 1991;Sandell et al, 1991;Su et al, 1991;Ng et al, 1993;Sandberg et al, 1993) and its presence or absence may result in structurally and functionally different extracellular matrices in these tissues. While the presence or absence of the exon 2-encoded domain does not affect the primary structure of mature type I1 collagen, this region of the amino propeptide has been thought to play a role in feedback regulation of collagen biosynthesis, the prevention of intracellular fibril formation, and in collagen fibril organization (reviewed by Ryan and Sandell, 1990).…”
Section: Type 111mentioning
confidence: 99%
“…Type I1 collagen transcripts have also been detected by RNA blotting or RT-PCR analysis in human and avian spinal ganglia, as well as in embryonic calvaria, diaphyseal bone, skin, muscle, lung, kidney, liver, small intestine, colon, brain, and heart (Cheah et al, 1991;Nah and Upholt, 1991;Sandell et al, 1991;Swiderski and Solursh, 199213, Ng et al, 1993;Sandberg et al, 1993). In the developing heart, type I1 collagen has been localized immunohistochemically at the interface between the epimyocardium and endocardium in stage ll embryonic chick hearts (Kosher and Solursh, 1989) and in stage E9 embryonic mouse hearts (Wood et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation